Pre-Slaughter Rest Is Effective in Improving the Physiology and Quality of Nile Tilapia Fillets Subjected to In Vivo Transportation at High Densities - Maria Ildilene da Silva; Valfredo Figueira da Silva; Marcio Douglas Goes; Sara Ugulino Cardoso; Leonardo Aluisio Baumgartner; Maria Luiza Rodrigues de Souza; Claucia Aparecida Honorato; Robie Allan Bombardelli; Elenice Souza dos Reis Goes (Foods)
This study evaluated the impact of transporting Nile tilapia at stocking densities of 250 kg/m3 and 500 kg/m3 for 1 h, with post-transport resting periods of 0, 2, 4, and 6 h, on biochemical parameters and fillet quality. A 2 × 4 factorial design was employed for the experiment, with 15 repetitions per treatment. The density of 500 kg/m3 resulted in a longer time to rigor mortis after 4 h of rest, while shorter rigor times were observed at 0 and 2 h. Fillets taken from fish transported at 250 kg/m3 for 4 h exhibited greater intensities of red and yellow color. The highest weight loss during cooking occurred in fish transported at 500 kg/m3 without rest. High-density stocking increased the pH of the fillets, reduced color intensity, and increased weight loss and drip loss. Resting periods of 4 and 6 h resulted in firmer fillets with improved water retention. Fish rested for 6 h at 250 kg/m3 recovered glycogen and glucose levels, indicating restored homeostasis. In contrast, fish subjected to high-density transport showed impaired metabolic recovery and compromised fillet quality. These results support the use of resting periods to improve fish welfare and product quality in aquaculture systems.